Analysis of A Tall Structure Considering Two Different Type of Dampers Using Analysis Tool - Jitesh Khatri; Dherendra Tiwari; Rakeh Patel (International Journal of Scientific Research in Civil Engineering, 2022)
Vibrations are one of the major environmental factors that act on buildings and mechanical structures, potentially reducing their lifetime. Current trends in construction industry demand taller and lighter structures with more flexibility, yet they have a quite low damping value. This increases failure possibilities and also create problems from serviceability point of view. Many building structure and bridges fall because of vibration, if frequency of excitation coincide with one of the natural frequency of system. Now-adays several techniques are available to minimize vibrations of a structure. Out of these, concept of using tuned mass damper is a recent trending innovation. This study is conducted to research the effectiveness of using tuned mass damper for controlling vibration of a structure. The report proposes a comparative analysis of passive vibration control system with inclined damper system and tuned damper system in G+15 structure where the modelling and analysis was done using ETABS.
Keywords: Vibration Control; Tuned Mass Damper (TMD); High Rise Buildings; Structural Design; Structural Analysis; Tuned Dampers